Al-Nadim’s (385 /995) Approach to Islamic Sects through his Monograph “al-Fihrist”: Pendekatan Al-Nadim (385 /995) terhadap Sekte-sekte Islam melalui Monografnya “al-Fihrist” - Mahmoud, Ramy (Aqwal: Journal of Qur'an and Hadis Studies, 2024)
Background and Objectives: The seeds of Islamic sects arose immediately after the death of the Prophet and the occurrence of wars between the companions, so each of these sects based their thoughts on a specific position they took in that war. When the number of sects and doctrines increased and different opinions spread in the Islamic faith, a group of Muslim scholars came out to record these opinions and write down the movements of the sects, whether geographically or historically, so as a result, what is called the Ilm al-Maqālāt arose, and this has become an essential part of many books written from the late second century Hijri calendar, some books were specially written in this field, such as the book of Maqālāt al-Islāmiyyin by Abu al-Hasan al-Ash'ari, while the Maqālāt became a part of other books. Methodology: Al- Nadīm is one of the authors who was concerned with the authorship movement during the three centuries of the Hijri calendar, so he intended to record all the books that fell into his hands in all fields, whether religious or non-religious. Al- Nadīm took care in all this to record the authorship movement of the famous Islamic sects, so he mentioned important information about Islamic sects such as Mu'tazila, Kharijites, Shiites and others, this information is related to the books written sometimes and other times related to the theologians themselves. Main Results: Our article monitored Al-Nadim's interest in this aspect. Research Contribution: This article was divided into an introduction, a conclusion, and three main headings; the introduction mentioned information about al-Fihrist by al- Nadīm, while the main headings dealt with al- Nadīm's life and information about him, the second heading discussed the section on the theologians, and sects, and the last heading shed light on the sources used by al- Nadīm in this section. Conclusion: This study underlines the importance of al-Nadīm's work in documenting the intellectual and theological history of Islamic sects, providing a foundational reference for scholars in Islamic studies and historiography.